A Hermeneutic Analysis of Serat Wicara Keras in the Context of Indonesian Political Dynasties - John Abraham Ziswan Suryosumunar; Arqom Kuswanjono; Mustofa Anshori Lidinillah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
The phenomenon of political dynasties is a contemporary issue that continually generates controversy, particularly with regard to moral legitimacy and the personalization of power within democratic practices in Indonesia. The ethical heritage of Javanese literature offers a value framework that is relevant to this issue, one of which is the value of nobility as taught in Serat Wicara Keras. This article is the result of research that applies the hermeneutic method to reveal the teachings of the value of nobility in Serat Wicara Keras as the formal object of the study, with the phenomenon of political dynasties in Indonesia serving as the material object. Library research was employed as the data collection method, beginning with planning, data inventory, data analysis, and classification. The results of the study are as follows: (1) Serat Wicara Keras is a literary work written by Yasadhipura II within the context of Javanese feudal culture. The work reflects Yasadhipura II’s critical reflection on social conditions during the leadership of Pakubuwana IV as the successor of the Islamic Mataram dynasty. (2) The value of nobility in Serat Wicara Keras is referred to as awirya, which constitutes the principal value that must be realized in order to avoid bilai (calamity). According to Yasadhipura II, nobility is not grounded in lineage, but in how an individual undertakes spiritual and ethical discipline (lelaku) until achieving mental and spiritual readiness for attaining nobility. (3) The practice of political dynasties in Indonesia is rooted in a culture of patronage and political personalization found in the leadership of several political parties. Yasadhipura II views the occurrence of political dynasties as a natural phenomenon; however, such dynasties must maintain nobility by adhering to processes that conform to the established moral order and principles.